Geological Development of the Continental Margin of Atlantic Canada - King, Lewis; Hyndman, Roy; Keen, Charlotte (Geoscience Canada, 1975)
Summary The continental margin of Atlantic Canada was formed by the rifting of continental masses in some areas and by the strike-slip motion between continental blocks in others. These motions imparted different structural characteristics to the basement. The subsequent development of the margins was controlled by thermal contraction and sediment loading which caused subsidence. These processes led to the formation of the East Coast Geosyncline. The geosyncline is divisible into a miogeociine encompassing the Mesozoic-Cenozoic succession underlying the continental shelf, and a eugeocline comprising strata of similar age underlying the continental rise and abyssal plain. The boundary between the miogeociine and eugeocline is in many areas represented by the modern and ancient continental slope.